Chapter La commercializzazione del vino e dell'olio in Italia settentrionale attraverso lo studio dei daziari tardomedievali - RAO, Riccardo (Reti Medievali E-Book, 2021)
The contribution reconstructs the wine and oil trade in Northern Italy, starting from the analysis of late medieval tariff books. The tariff books of the major cities are characterised by a wide range of wine products, which included Greek wines, but also wines traded regionally. Olive oil together with linseed oil constitutes the most important variety among cooking oils.